An Immobilized Enzyme Approach to Anti-Microbial Peptide Production - Kirkendoll, Josephine A (My University, 2025)
The rise in resistance to common antifungal agents has highlighted the need for alternative therapeutic options. Antimicrobial peptides (AMPs) have gained attention due to their broad-spectrum antimicrobial properties and low toxicity. Among these, Histatin-5 has shown potent activity against Candida albicans, including strains resistant to standard treatments. This research focuses on synthesizing and isolating bioactive Histatin peptides via protein overexpression in E. coli. Rather than using the full-length peptide, P113 was employed, a 12-amino acid fragment of Histatin-5 that retains strong antifungal activity due to its increased stability and ease of production. Our immobilized protease method has proven effective in expressing and isolating small quantities of P113. Current efforts, in collaboration with East Carolina University’s School of Dental Medicine, are aimed at scaling up Histatin-5 production and exploring the antimicrobial properties of recombinant P113 peptides. Future work will characterize the antimicrobial activity of these peptides and investigate gel-based formulations for oral delivery, potentially establishing a novel approach to oral health treatments.
Keywords: Antimicrobial peptides; Histatin-5; Candida albicans